CONSUMPTION BEHAVIOR OF FARMER HOUSEHOLDS IN RURAL SUMBAWA, INDONESIA - Budiman Achmad; Dian Diniyati (Indonesian Journal of Forestry Research, 2018)
The welfare level of farmer in rural Sumbawa was steadily low although the potency of natural resources at their vicinity was high. This paper determines the consumption behaviour  as well as the welfare level a farmer households in rural Sumbawa, Indonesia. The household size, years of education, and farming incomes were used as indicators of on-farm performance. This research was carried out in February until April 2015 at two separate forest areas which were administratively under Labuhan Badas village, i.e.  community forestry (HKm) in the state production forest and private owned forests (POF). A number of 34 respondents perlocation were purposively selected. The multiple linear regression was implemented to analyze factors affecting farmer household consumption behaviour, while the exchange value for income earned by farmer (EVIF) was incorporated to measure the welfare level. The regression revealed that the consumption behaviour  at two groups of respondents were positively related with three indicators, i.e. household size, years of education, and farming incomes.  Meanwhile, the household size affected the consumption behaviour  of the HKm farmers but not the POF farmers.  Furthermore, the consumption is strongly affected by the income generated from both forest areas. The EVIF approach revealed that the welfare of whole farmers were still low (EVIF = 0.74-0.99). The government, therefore, should subsidize rain fed paddy and tobacco seeds varieties which are suitable with the local climate, while the farmers are trained to process the flesh of cashew fruit into wine or chips and encouraged to cultivate calliandra trees for apiculture development and wood pellet or charcoal production.